1995
DOI: 10.1111/j.1365-3180.1995.tb01629.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hypoxia on buried weed seed germination

Abstract: Summary Trials were carried out in order to investigate the effect of hypoxia on seed germination of Datura stramonium L. in Petri dishes and when buried at various depths in soil. Hypoxia was found to cause a decrease in germination capacity and germination rate. This inhibition was partially alleviated by daily exchange of hypoxic gas surrounding the seeds during incubation. Similarly, seed scarification allowed maintenance of a higher germination capacity under conditions of low oxygen availability, showing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
82
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(86 citation statements)
references
References 42 publications
4
82
0
Order By: Relevance
“…Hypoxia is another factor which can induce dormancy (Benvenuti and Macchia 1995, Pekrun et al 1997, Momoh et al 2002. Sandy soils with greater pore volume and gas exchange facilitated emergence of Datura stramonium, whereas emergence was inhibited by clay soils (Benvenuti 2003).…”
Section: Conventionalmentioning
confidence: 99%
“…Hypoxia is another factor which can induce dormancy (Benvenuti and Macchia 1995, Pekrun et al 1997, Momoh et al 2002. Sandy soils with greater pore volume and gas exchange facilitated emergence of Datura stramonium, whereas emergence was inhibited by clay soils (Benvenuti 2003).…”
Section: Conventionalmentioning
confidence: 99%
“…Exceptions are the species (Kennedy et al 1991) and Datura stramonium L. (Benvenutti & Macchia 1995).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, it has been noted (Terpstra, 1995) that compaction of soil aggregates plays a crucial role in germination inhibition. Alhough the ecophysiological causes of this phenomenon have not yet been fully clarified, it is probably due to poor soil gas diffusion (Benvenuti and Macchia, 1995). Other studies have shown that in such conditions even phytochrome activation (of photosensitive seeds) by light stimuli becomes ineffective (Benvenuti and Macchia, 1997).…”
Section: Resultsmentioning
confidence: 99%
“…Preservation of seeds in the soil is also favoured by the frequent limitations on key germination factors such as temperature (Vleeshouwers, 1997), water (Forcella, 1993), light (Taylorson and Handricks, 1983) and oxygen (Benvenuti and Macchia, 1995). The latter factor is thought to be strongly involved in the germination trigger as a result of aereation created through soil tillage.…”
Section: Introductionmentioning
confidence: 99%